(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the modern world, automobiles play a significant role in daily life. Every family needs it on a basic level. Imagine having to travel hundreds of miles on foot over the course of several days, but because to the invention of the automobile, transportation is now much faster, simpler, and more dependable. There aren’t enough chips left for the car industry. Due to the lengthy lead times for the tiny silicon chips, production of everything from smartphones and home appliances to driver-assistance systems has been hampered, leading to the global semiconductor crisis that started in the first quarter of 2021. The study’s findings show how the decline in semiconductor sales affected India’s vehicle market.